Randomised clinical trial of an emergency department-based peer recovery support intervention to increase treatment uptake and reduce recurrent overdose among individuals at high risk for opioid overdose: study protocol for the navigator trial. Issue 11 (11th November 2019) - Goedel, William C; Marshall, Brandon D L; Samuels, Elizabeth A; Brinkman, Mark G; Dettor, Debra; Langdon, Kirsten J; Mahoney, Linda A; Merchant, Roland C; Nizami, Tarek; O'Toole, George A; Ramsey, Susan E; Yedinak, Jesse L; et al.
Abstract : Introduction: Effective approaches to increase engagement in treatment for opioid use disorder (OUD) and reduce the risk of recurrent overdose and death following emergency department (ED) presentation for opioid overdose remain unknown. As such, we aim to compare the effectiveness of behavioural interventions delivered in the ED by certified peer recovery support specialists relative to those delivered by licensed clinical social workers (LCSWs) in promoting OUD treatment uptake and reducing recurrent ED visits for opioid overdose. Methods and analysis: Adult ED patients who are at high risk for opioid overdose (ie, are being treated for an opioid overdose or identified by the treating physician as having OUD) (n=650) will be recruited from two EDs in a single healthcare system in Providence, Rhode Island into a two-arm randomised trial with 18 months of follow-up postrandomisation. Eligible participants will be randomly assigned (1:1) in the ED to receive a behavioural intervention from a certified peer recovery support specialist or a behavioural intervention from an LCSW. The primary outcomes are engagement in formal OUD treatment within 30 days of the initial ED visit and recurrent ED visits for opioid overdose within 18 months of the initial ED visit, as measured through statewide administrative records. Ethics and dissemination: This protocol was approved by the Rhode Island Hospital institutional review board (Approval Number: 212418). Data will be presented at national and international conferences and published in peer-reviewed journals. Trial registration number: NCT03684681 .